Monitoring of post-vaccination anti-HBs titles vaccine in children and adolescents in the pre-dialysis of chronic kidney disease - Nathália Cristina Pereira da Costa; Mônica Ribeiro Canhestro; Cristina Maria Bouissou Morais Soares; Juliana Scudilio Rodrigues (Brazilian Journal of Nephrology, 2017)
Abstract Introduction: Bacterial or viral diseases are one of the major causes of death in patients with chronic kidney disease (CKD). These patients show a quantitative reduction of levels of antibodies over time. Among the infectious diseases that affect CKD patients, stands out hepatitis B (HB). Immunization and control of antibodies levels against the hepatitis B surface antigen (anti-HBs) are ways to prevent the HB infection in this population. Patients with anti-HBs levels ≥10 IU/ml are considered adequate responders, whereas those with anti-HBs levels ≥ 100 IU/ml are considered excellent responders. Objective: To analyze the variation of the anti-HBs levels obtained after vaccination against HB in children and adolescents in the pre-dialysis stage of CKD. Methods: A retrospective cohort study on anti-HBs levels of children and adolescents in the pre-dialysis stage of CKD. Correlation between levels of anti-HBs titers and time since the vaccination were estimated. Results: From the total of 116 studied patients most of the studied patients were considered excellent responders, obtaining in the three anti-HBs titers percentages of 70.7%, 62.1% and 54.9% respectively. The anti-HBs titer levels showed a negative correlation with the time since vaccination (Kendall Tau-b = -0.16; p = 0.02). Conclusion: The majority of the studied population was vaccinated by PNI and showed excellent anti-HBs titer levels, even experiencing a progressive reduced response over the time.